PENGARUH TIME BUDGET PRESSURE, KOMPETENSI, INDEPENDENSI, DAN INTEGRITAS TERHADAP KUALIAS AUDIT DENGAN KECERDASAN EMOSIONAL SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK KOTA PEKANBARU DAN PADANG) - Nurhasanah, Dinna; Hasan, Amir; Savitri, Enni (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2017)
This research was conducted with the aim to know the influence of Time BudgetPressure, Competence, Independence, and Integrity to Quality Audit. Then to findout whether Emotional Intelligence can moderate the relationship between TimeBudget Pressure, Competence, Independence, and Integrity to Quality Audit. Thisresearch was conducted at Public Accountant Office of Pekanbaru and Padang with45 samples. The method of data collection is to use the questionnaire list. While themethod of data analysis using multiple analysis and Moderated Regression Analysis(MRA) using tools SPSS version 21. The results showed that Time BudgetPressure, Competence, and Independence have a significant effect on audit quality.Integrity has no significant effect on audit quality. Then Emotional Intelligence canstrengthen the relationship between Competence, Independence, and Integrity withQuality Audit. But Emotional Intelligence can not strengthen the relationship of TimeBudget Pressure with Quality Audit.